The impact of tourism uncertainty on airline stock markets in Korea: a quantile regression approach - Jeon, Ji-Hong (Journal of Business Economics and Management, 2021)
This study explores the impact of tourism uncertainty, including economic policy uncertainty (EPU) and travel crises arising from issues such as terrorism and disease outbreaks, on airline stock markets in Korea. Airline stock prices are particularly affected by tourism uncertainty. Using data from 2001–2018 and events influencing tourism uncertainty such as the 9/11 terrorist attacks and severe acute respiratory syndrome, quantile regression approach reveals how EPU influences airline stock prices in Korea during three market phases – bearish, normal, and bullish. EPU and travel crises negatively affect airline stock prices in Korea. Specifically, we document that higher EPU and more global travel crises lead to deeper reductions in stock prices in bullish markets. These results provide implications and insights for airline investors, stakeholders, and organizations concerned about the influence of tourism uncertainty on airline stock prices in Korea.